Results of transaxillary endoscopic surgery of the thyroid gland in Peru - Díaz, Alvaro (2021)
Objective: To describe the results of transaxillary endoscopic surgery of the thyroid gland without insufflating CO2 in Peru. Methods: A retrospective case series based of chart review of patients with thyroid cancer undergoing transaxillary endoscopic surgery of the thyroid gland without insufflating CO2 from November 2014 to March 2017 in public and private institutions in Lima. Results: 24 transaxillary endoscopic procedures were performed, 15 of which were hemithyroidectomies, 8 were total thyroidectomies and one subtotal thyroidectomy. Mean operating time was 193.8 minutes. The most common complication was post operatory hematoma (12.5%) followed by transient hypocalcemia (8.3%), no lesions of the brachial plexus were observed. Conclusions: Transaxillary endoscopic surgery of the thyroid gland is a safe and feasible procedure to be performed in equipped centers.